Induced polarization of volcanic rocks. 4. Large-scale induced polarization imaging. Issue 2 (14th January 2021) - Gross, L; Soueid Ahmed, A; Revil, A
SUMMARY: Thanks to the emergence of new technologies developed with the goal of performing large-scale galvanometric induced polarization surveys and thanks a better understanding of the underlying physics of induced polarization, this geophysical method can now be applied in the field of volcanology and geothermal resources assessment. A new approach is developed here for directly inverting the primary and secondary electric fields recorded at a set of independent stations when injecting a primary current. The use of independent stations to measure the primary and secondary electrical fields improves the quality of the data by reducing the capacitive coupling effects inherent to systems based on long cables. It avoids issues associated with using the same electrodes for both current injection and voltage measurements and negative apparent resistivity and chargeability values. With such acquisitions, we can perform true 3-D surveys in areas characterized by complex topography such as volcanoes. The numerical scheme we developed returns as output the electrical conductivity and chargeability fields. The implemented methodology presents several advantages. The first is the use of data types at the stations, for example the electric field intensity, that are independent from the local geometrical station parameters such as electrode spacing and dipole orientation. The second advantage lies in the suitability of the proposed approach to perform large-scale applications since we use a matrix-free approach that does not require the assembly of the Jacobian matrices. The third concerns the possibility of performing the inversion on complex geometries through a consistent use of the finite element method on unstructured meshes in combination with algebraic multigrid preconditioning for the regularization and the solution of the forward and adjoint problems. The computation of 3-D sensitivity maps can also be a real asset in survey design. After validating our approach with a benchmark synthetic case study, we test it on a large-scale induced polarization survey that mimic true field conditions on a volcanic environment with rough topography. Our tests demonstrate the high potential of this electric field approach in volcanology especially for deep (3 km) imagining of the internal structure of volcanoes, which in turn could improve our understanding of hydrothermal systems and allow the monitoring of active volcanoes and the potential risk of collapse.